Does it pay to play by the rules? Respect for rule of law, control of corruption, and national success at the summer Olympics - Potts, T. B. (Journal of Sports Economics, 2022)
Utilizing the set of World Governance Indicators published by the World Bank, this paper finds that scoring highly in an indicator measuring respect for rule of law and control of corruption is associated with fewer athletes disqualified and higher medal shares at the Summer Olympics from 1996-2016. Notable reductions in disqualifications and increases in medal shares occur at coincident percentile ranks in the aforementioned indicator, with nations at the 67th percentile rank and above having a 13.8% higher probability of medaling and a 12.11% lower probability of having an athlete disqualified. These results uncover a new link between governance and Olympic success and provide support for the existing anti-doping rules and enforcement as, ceteris paribus, it would seem that nations whose athletes respect and abide by the rules achieve higher medal shares than those whose athletes do not.